A New Computational Tool for Analyzing Translation Processes: The TransCorrect Project - Colson, Jean-Pierre (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe TransCorrect project is a first attempt to automate the correction of human translation within the context of higher education. It is based on a number of new techniques derived from computational corpus linguistics, but also on the author’s pedagogical experience. The program was specially created for the teaching of translation at university level. While offering the students an immediate feedback to their translation attempts, the TransCorrect project also enables the teacher to have an additional insight into the complex translation processes.